2013
DOI: 10.1097/acm.0b013e318294f817
|View full text |Cite
|
Sign up to set email alerts
|

Are Medical Students Aware of Their Anti-obesity Bias?

Abstract: Purpose Anti-obesity prejudices affect the quality of care obese individuals receive. The authors sought to determine the prevalence of weight-related biases among medical students and whether they were aware of their biases. Method Between 2008 and 2011, the authors asked all third-year medical students at Wake Forest School of Medicine to complete the Weight Implicit Association Test (IAT), a validated measure of implicit preferences for “fat” or “thin” individuals. Students also answered a semantic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 48 publications
(48 reference statements)
13
64
0
Order By: Relevance
“…Research investigating the attitudes of medical students found that approximately 40% of students had significant weight bias, and that two thirds of these students were unaware of their bias (Miller et al, 2013). Similar results have been found with students in other health fields including nursing and psychology students (Waller et al, 2012), dietetics students ) and exercise science students (Chambliss et al, 2004).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Research investigating the attitudes of medical students found that approximately 40% of students had significant weight bias, and that two thirds of these students were unaware of their bias (Miller et al, 2013). Similar results have been found with students in other health fields including nursing and psychology students (Waller et al, 2012), dietetics students ) and exercise science students (Chambliss et al, 2004).…”
supporting
confidence: 72%
“…Given the pervasiveness of weight bias in North American society (Puhl & Heurer, 2009) and the dramatic increase in the occurrence of weight bias in recent years Puhl et al, 2008), it is not surprising that health professionals and students are not immune to weight bias (e.g., Miller et al, 2013;Sabin, et al, 2012). Although efforts have been made to reduce weight bias in health professionals (e.g., Poustchi et al, 2013;Rukavina et al, 2010), these programs and interventions are short-term efforts and have not yet been integrated systemically into training curricula.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some individual traits may make us more or less aware of our implicit biases, it is important to note that awareness of implicit biases is a necessary but not sufficient condition for behavioral change. Extant research supports the notion that everyone has implicit and automatic stereotypes that may contribute to expressing prejudice in subtle ways (Madera & Hebl, 2012;Miller et al, 2013).…”
Section: Perpetrator Experience Of Subtle Discriminationmentioning
confidence: 85%
“…Preclinical medical students are thus good examples of the effects of both implicit (unconscious) and explicit ( conscious) weight bias. Surveys show more than 40 % of medical students have signifi cant implicit weight bias [ 82 ], yet few are aware of their bias [ 83 ]. Unfortunately, the degree of weight stigma does not decrease with accumulating medical education or clinical experience.…”
Section: Weight-related Stigma In the Healthcare Systemmentioning
confidence: 99%